Trust and emergency management: Experiences from the Arctic Sea region. Issue 2 (3rd July 2019) - Roud, Ensieh; Gausdal, Anne Haugen
ABSTRACT: Trust has long been identified as an essential component in different disciplines. However, trust in the context of emergency management is a less often researched phenomenon. This article intends to enrich our theoretical understanding of trust by exploring the role of interorganisational trust and the process of trust development across phases of emergency management. To achieve this, a critical case study of the cross-national Arctic Sea region is conducted. The findings reveal that in each phase of emergency management, trust has a critical role to play such as improving coordination, communication, reliability and learning. Moreover, a cross-level framework for trust development is presented in order to illustrate how each phase of emergency management contributes to process theories of trust. The article explicates how the preparation phase contributes to developing interorganisational trust. The response phase contributes significantly to developing swift interorganisational trust. Although the evaluation phase has significant potential to transform this swift and fragile trust into a more resilient interorganisational trust, this potential is underexploited due to the low priority accorded to this phase. The article elaborates on trust in the emergency context and brings the group and project level concept of swift trust to the interorganisational level of analysis.